The prevalence of low vitamin D in elite para-athletes: A systematic review - Langley, C. K.; Morse, K. I.; Buffey, A. J. (Sports Medicine - Open, 2024)
Background Vitamin D insufficiency (25OHD, 50-75 nmol*l- 1) is a common issue within healthy adults and elite athletes and is associated with decreased musculoskeletal health and performance. However, few studies have identified the prevalence and risk factors associated with vitamin D insufficiency within elite Para-Athletes.